Lasianobia nainysi, a new species from Sichuan, China (Lepidoptera, Noctuidae, Noctuinae) - Saldaitis, Aidas; Volynkin, Anton V.; Zahiri, Reza (Zootaxa, 2021)
A new species of the genus Lasianobia Hampson, 1905, Lasianobia nainysi Saldaitis, Volynkin & Zahiri, sp. nov. is described from highlands of western Sichuan Province of China. The new species is closely related to Lasianobia albilinea (Draudt, 1950). Adults, male and female genitalia as well as DNA barcode data of the new and related species are presented.